Improving antioxidant scavenging effect of fruit peel waste extracts and their applicability in biodiesel stability enhancement - Usman Bello; Nurul Aini Amran; Muhammad Syafiq Hazwan Ruslan (Journal of Saudi Chemical Society)
The increasing popularity of fruit peel extracts as effective sources of natural antioxidants is primarily attributed to their affordability, easy availability, and high phenolic contents that readily dissolve in solutions. However, most natural antioxidants demonstrate a lesser free radical scavenging effect when applied in mono blends compared to their synthetic counterparts. To address this problem, this work aims to improve the antioxidant capacities of palm fruit, banana, and mango peel liquid extracts recovered using supercritical fluid extraction (SFE). Firstly, a reverse-phase high-performance liquid chromatography (RP-HPLC) was used to isolate three (3) target bioactive compounds from the extracts, whose estimated quantities ranged between 1.2983–4.6841, 1.1469–3.6987, and 0.0254–0.0489 mg/g for quercetin, beta-carotene, and gallic acid respectively. Subsequently, blends of the recovered extracts were formulated in mono, binary, and ternary dosage ratios (S.1–S.10) to assess their free radical scavenging efficiency (RSE) in terms of inhibitory concentration at 50% (IC50) using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, total phenolic content (TPC), total flavonoid content (TFC), and total carotenoid content (TCC). Based on the results obtained, the highest RSE was exhibited by the ternary blend (S.9), with an IC50 value of 76.21 ± 032 µg/mL and a TPC value of 242.38 ± 0.26 mg gallic acid equivalent (GAE/g). The fastest kinetics for the extracts’ reaction with DPPH corresponding to a rate constant (K) of 1.2351 M−1.min−1 and activation energy (Ea) of 0.55 KJ/mol were presented by the same sample blend (S.9), indicating the ease of hydrogen atom release for radical scavenging. Finally, the peel extracts demonstrate an improved antioxidative performance by prolonging the biodiesel’s induction period of the extracts-blended samples as obtained from Rancimat analysis.